2018
DOI: 10.3389/fphar.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide Produced by Probiotic Strain Lactobacillus paraplantarum BGCG11 Reduces Inflammatory Hyperalgesia in Rats

Abstract: The aim of this study was to test the potential of high molecular weight exopolysaccharide (EPS) produced by the putative probiotic strain Lactobacillus paraplantarum BGCG11 (EPS CG11) to alleviate inflammatory pain in Wistar rats. The EPS CG11 was isolated from bacterial surface and was subjected to Fourier-transform infrared spectroscopy (FTIR) and thermal analysis. FTIR spectra confirmed the polysaccharide structure of isolated sample, while the thermal methods revealed good thermal properties of the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
335
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(346 citation statements)
references
References 49 publications
8
335
3
Order By: Relevance
“…Similarly to CF tissue, pHBE CF cells show increased levels of mesenchymal markers, although not accompanied by decreased levels of epithelial markers. Consistently, TEER values (an indicator of integrity of HBE cell cultures 43 ) were significantly lower in CF vs non-CF pHBE cells (Fig. 2C ), indicative of a leaky epithelium and suggesting impaired organization of cell-cell junctions in CF.…”
Section: Resultssupporting
confidence: 55%
“…Similarly to CF tissue, pHBE CF cells show increased levels of mesenchymal markers, although not accompanied by decreased levels of epithelial markers. Consistently, TEER values (an indicator of integrity of HBE cell cultures 43 ) were significantly lower in CF vs non-CF pHBE cells (Fig. 2C ), indicative of a leaky epithelium and suggesting impaired organization of cell-cell junctions in CF.…”
Section: Resultssupporting
confidence: 55%
“…Previous studies have suggested that the over-production of reactive oxygen species (ROS) may have complex roles in promoting the development of age-related diseases [7]. In addition, the cellular elevation of ROS has been associated with the onset and progression of ageing [8]. Meanwhile, it is widely accepted that ROS not only cause oxidative damage, but are also involved in normal cellular function as signalling molecules, through the oxidation of functional thiols on target proteins [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…C. majus is a plant of great interest for its wide use in folk medicine and also in official phytotherapy. This species is known to synthesize a broad range of secondary metabolites which provide its therapeutic properties [ 3 ]. The most common group of these secondary metabolites are isoquinoline alkaloids (1–2% in the herb and 2–4% in the roots), including chelidonine, berberine, sanguinarine, coptisine, chelerythrine and protopine [ 4 ].…”
Section: Introductionmentioning
confidence: 99%